2018
DOI: 10.1111/gcb.14290
|View full text |Cite
|
Sign up to set email alerts
|

Ocean warming has a greater effect than acidification on the early life history development and swimming performance of a large circumglobal pelagic fish

Abstract: Ocean warming and acidification are serious threats to marine life; however, their individual and combined effects on large pelagic and predatory fishes are poorly understood. We determined the effects of projected future temperature and carbon dioxide (CO ) levels on survival, growth, morphological development and swimming performance on the early life stages of a large circumglobal pelagic fish, the yellowtail kingfish Seriola lalandi. Eggs, larvae and juveniles were reared in cross-factored treatments of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 71 publications
6
53
1
Order By: Relevance
“…Such a pronounced interspecies variability is possibly due to different experimental setups, different analysed life stages (often limited to very early life stages, e.g., embryos, nonfeeding larvae), and short-term versus long-term effects of the applied treatments. For example, no effect on growth rate was observed for walleye pollack (Theragra chalcogramma; Hurst, Fernandez, & Mathis, 2013), juvenile scup (Stenotomus chrysops; Perry et al, 2015) and the larvae of yellowtail kingfish (Seriola lalandi; Watson et al, 2018). For other species, a decrease in growth rate under elevated CO 2 was observed, for example in the inland silverside (Menidia beryllina; Baumann, Talmage, & Gobler, 2012), for yellowfin tuna (Thunnus albacares; Bromhead et al, 2015), and Atlantic herring (Clupea harengus; Frommel et al, 2014).…”
mentioning
confidence: 99%
“…Such a pronounced interspecies variability is possibly due to different experimental setups, different analysed life stages (often limited to very early life stages, e.g., embryos, nonfeeding larvae), and short-term versus long-term effects of the applied treatments. For example, no effect on growth rate was observed for walleye pollack (Theragra chalcogramma; Hurst, Fernandez, & Mathis, 2013), juvenile scup (Stenotomus chrysops; Perry et al, 2015) and the larvae of yellowtail kingfish (Seriola lalandi; Watson et al, 2018). For other species, a decrease in growth rate under elevated CO 2 was observed, for example in the inland silverside (Menidia beryllina; Baumann, Talmage, & Gobler, 2012), for yellowfin tuna (Thunnus albacares; Bromhead et al, 2015), and Atlantic herring (Clupea harengus; Frommel et al, 2014).…”
mentioning
confidence: 99%
“…The CO 2 treatments were the currentday ambient conditions for each temperature (462 and 538 µatm for 21 and 25°C, respectively) and an elevated CO 2 treatment of approximately 1000 µatm CO 2 to match projections under RCP 8.5 (Collins et al 2013) (Table 1). Previous results from this experiment have demonstrated increased activity, metabolic rate and growth rate, but reduced survivorship of larval and juvenile kingfish at 25°C relative to 21°C (Laubenstein et al 2018, Watson et al 2018. By contrast, 1000 µatm CO 2 had no effect on activity, growth or survival, but did affect metabolic rate and swimming performance (Laubenstein et al 2018, Watson et al 2018.…”
Section: Introductionmentioning
confidence: 54%
“…The broodstock were fed a mixture of pilchard (Sardinops sagax) and squid (Notodarus spp.). For further details, all broodstock, egg, and larval maintenance protocols followed Watson et al [15]. The offspring used for this experiment were collected from a spawning event on the night of 23 January 2017.…”
Section: Study Species Broodstock Egg and Larval Maintenancementioning
confidence: 99%
“…For instance, Domenici et al [13] found that elevated CO 2 and temperature have different and interacting effects on behavioral lateralization in reef fishes, whereas Munday et al [14] found that elevated CO 2 and temperature have additive effects on metabolic rates in two species of cardinalfishes. Other studies point towards temperature having a greater overall effect on ontogenetic development, swimming ability [15], and the outcome of predator-prey interactions [16] compared with elevated CO 2 . Therefore, it is necessary to consider the interacting effect of warming to properly understand the effects of ocean acidification on fishes and predict outcomes for the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation